(untitled) (Південний архів (історичні науки), 2023)
Purpose. The purpose of the article is to research the migration process of Swedish peasants from Estonia to Southern Ukraine and creation of Swedish colony in Ukrainian steppe. This question is not researched quite enough in historiography. Events before and after resettlement are illuminated rather good, but what was happening during migration and few months after it was unknown. Nevertheless, historical sources enables to research events during this period sufficiently deep. For instance, captain’s Egor Makaretov logbook in very informative source about Swedish resettlement to Southern Ukraine. He was a head of soldier’s convoy of these migrants group from Estonia to the place of the settlement. For a long time researches did not put it into account through bad quality of microfilm copy of the document. Lists of migrants and colonists also gives important information. Methods. Method of contamination information from different lists was used in the research. Comparing information from different sources was also helpful. It gives an opportunity to detect changes at the composition of the households and to identify persons have died during some time intervals. Criticism of the sources and the method of slow reading helped to avoid some erroneous judgments. Results. The research established that the mostly probable estimate of Swedish migrant’s group population size is 967persons. The way from Estonia to Ukraine could not lay through Moscow. It was passed through Belorussia, Chernigiv region and then – though Eastern Ukraine to the city Novyi Kodak (modern Dnipro city), where migrants crossed river Dnipro. The large part of the Swedish migrants have died in winter 1781-1782 years at the Reshetylivka city (Poltava region). Conclusions. Author makes the conclusion that some aspects of Swedish resettlement to the South of Ukraine include elements of historiographical myths. Among these cases are: number of migrants, the way Swedish colonist’s passed during their trip, resettlement conditions and reasons of migrant group population size decrease. Contrary to some historiographical references, the sources demonstrate that Russians tried to provide good feed and treatment for Swedish colonists during their trip, but the level of medicine knowledge do not allow them to curb the mortality effectively. Simultaneously authority did not manage to provide the colonists with housing in time. Some of created houses were incomplete even after a year after resettling and colony’s creation.